Effect of Density on Consolidation and Creep Parameters of Clay - Alhaji, Mustapha Mohammed; Alhassan, Musa; Adejumo, Taiye Waheed; Jibrin, Ramatu (Indonesian Journal of Science and Technology, 2020)
Effect of density on consolidation and creep parameters of a clay soil was investigated using a soil classified according to Unified  Soil  Classification  System  (USCS)  as  Clay  of  High plasticity (CH) and composing majorly of secondary minerals, including montmorillonite. The air-dried soil was compacted at five different compaction energy levels (Reduced Standard Proctor compaction energy, Standard Proctor compaction energy, West African compaction energy, Reduced Modified Proctor  compaction  energy,  and  Modified  Proctor compaction energy). Specimens for consolidation tests were molded  at  the  five  different  compaction  energy  levels (densities). The consolidation parameters (initial void ratio, compression  index,  and  preconsolidation  pressure)  were observed to be empirically related to the compaction energy. The  creep  parameters  (i.e.  primary  compression  index, secondary compression index, and magnitude of creep) were observed to increase with increases in loading to 387kN/m2, after  which  the  values  decreased.  Curves  resulting  from these relationships were observed to increase with increases in compaction energy level and tent towards straight line at Modified Proctor compaction energy. Maximum magnitude of creep estimated for three years was observed to reduce from 455.5 mm at Reduced Standard Proctor compaction energy through 268 mm at West African compaction energy to 247.4 mm at Modified Proctor compaction energy levels.